Antibacterial Activity and Kinetic Release of Laureliopsis philippiana (Looser) Essential Oil from Nanostructured Porous Silicon with Surface-Functionalization Alternatives - Andrés Pérez-San Martín; Karina Uribe; Jacobo Hernández-Montelongo; Nelson Naveas; Miguel Manso-Silván; Patricio Oyarzún; Víctor Díaz-García; Braulio Contreras; Gonzalo Recio-Sánchez (Applied Sciences, 2022)
In this work, the antibacterial activity of Laureliopsis philippiana (Looser) essential oil was studied, and its kinetic release performance using different surface-functionalized nanostructured porous silicon (nPSi) was analyzed. Experimental results showed the high inhibitory effect of Laureliopsis philippiana essential oil against Staphylococcus aureus and Klebsiella pneumoniae. In addition, the essential oil was successfully loaded into different kinds of functionalized nPSi. FTIR measurements indicated the formation of stable complexes in the nPSi functionalization process. Specifically, chemical oxidized nPSi (nPSi-Ox), 3-aminopropyltriethoxysilane functionalized nPSi (nPSi-APTS), undecylenic acid-functionalized nPSi (nPSi-UAc), chitosan (nPSi-Chi) and β-cyclodextrin (nPSi-βCD) polymer functionalization on nPSi were studied. nPSi-Ox, nPSi-APTS, and nPSi-UAc were covalent functionalization, and nPSi-Chi and nPSi-βCD were obtained by electrostatic attachment. The kinetic study demonstrated a controlled release of up to 4 h for all the samples following a quasi-Fickian diffusion mechanism. Moreover, the use of functionalized nPSi-APTS and nPSi-UAc structures allows a more controlled kinetic release of Laureliopsis philippiana essential oil in comparison to the rest of the functionalization, increasing its availability and exposure to the environment.